Sustained clinical response after single course of rituximab as first-line monotherapy in adult-onset asthma and periocular xanthogranulomas syndrome associated with IgG4-related disease: A case report. Issue 26 (June 2018) - Pomponio, Giovanni; Olivari, Diletta; Mattioli, Massimo; Angeletti, Alessia; Rossetti, Giulia; Goteri, Gaia; Gabrielli, Armando
Abstract: Rationale: IgG4-related disease (IgG4-RD) is an emerging immune-mediated disease characterized by multi-organ involvement and variable clinical behavior. Patient concerns: We describe the case of a 50-year-old woman affected by a rare variant of IgG4-RD, characterized by eyelid xanthelasmas, adult-onset asthma and salivary and lacrimal glands enlargement. Multiple lymphadenopathies and a pulmonary mass were present at initial evaluation. Inteventions: After a single course of rituximab (2g in 2 refracted doses), an almost complete clinical remission was achieved without chronic steroid administration. Outcomes: Magnetic resonance imaging (MRI), high-resolution computed tomography (HRCT) of the thorax, and positron emission tomography (18FDG-PET-CT) confirmed good response to treatment. Circulating plasmablasts dropped to undetectable levels as well. Xanthelasmas only remained unchanged. Remission persisted at 1-year follow-up. Lessons: Steroid therapy is still considered standard first-line therapy in IgG4-RD. However, high doses are generally required and relapses are common during the tapering phase. Rituximab is a well described steroid-sparing strategy, so far reserved to refractory cases only. In our experience, rituximab has been used as first-line monotherapy, showing great and sustained efficacy and optimal tolerability. The peculiar variant of IgG4-RD affecting our patient, the relatively low baseline plasmablast concentration, and the early placement of rituximab therapy may have facilitated the good response.